Employees Respect and Job satisfaction in Nepalese Private College - Mishra, Sanjib; Mahat, Dipak; Khanal, Lekhanath (Nepal Journal of Multidisciplinary Research, 2021)
Respect is the bedrock of humanitarian and ethical behavior, and mutual respect is the bedrock of healthy relationships. Respect for another person entails a basic conviction in their right to exist, be heard, and have equal chances as everyone else. With linked with the statement the main aim of the study is to examine the employees respect and job satisfaction in Nepalese private college. The research was done utilizing a structured questionnaire survey. The information was gathered from 400 members of the teaching and non-teaching staff at private institutions. The Cronbach's Alpha value was used to verify the dependability of the acquired data. The data was analyzed using percentages, means, and correlations. Finding of the study shown that the majority of respondents were happy with their colleague's respect, the respect of the entire college, and the respect of other departments inside the organization. Similarly, respondents appreciate their colleague, their college, and other departments in the organization. Furthermore, it was found that respect and employee satisfaction are significantly correlated, as p 0.000, which is less than 0.01 significant levels. In that r=0.376, which show there is a need to enhance in relevant employee behaviors inside the corporate atmosphere.